(3GdGSJYOGO deQJHI GdELJgGOs - (3LeGd GdOjf eMeO Hf Ydj Hf YHO Gddg GdehRYj Gdjefj, GHf fhQ GdOjfs ((3GdUOjb YeQ TeGN s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd dYHjOg ai cd TF SHHkG , hLYd dge Edi cd UfYI eONdkG hePgHkG s
(3BNQgG (B:s
(3dCf eHfi GdMOhO Ydi GdOQA hGdESbGW HGdTHgGJ Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdfSNI HQSe Gdabjg Yaja GdOjf YHO Gddg Hf eMeO Hf CHj HcQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdSjO eMeO Hf eMeO Hf YHO GdbGOQ GdCgOd GdNGUg HJYR s
Keywords: (3Gdabg GdESdGejs